Legal Liability for Importers in Making Payments Through the Telegraphic Transfer System at PT. Sumatera Ocean Transindo - Syawal Lubis, Muhammad; Sitompul, Ariman; Ruslaan, Ruslan (International Asia Of Law and Money Laundering (IAML), 2024)
In digital All Access is easy to do activities.Combining relations between parties in an international context is not an easy affair. It involves differing systems,views, and judgments that act as standards that must be adhered to by parties in different countries. Transacting in the context of international business at this time is not a difficult thing,because various technological advances have opened up huge opportunities for the international community to relate to each other. However, this ease can also cause various problems between them.International business is a convict state, where convicts grant broad freedom to the parties concerned to make, negotiate, and enforce the clauses they agree to. However, it is important to recognize that in order to carry out such business activities, the parties must carefully understand the rules of law in force in the opposing country. This will have a significant impact on the implementation of the agreement. Therefore, it is very important for researchers to clarify legal protections in international business transactions in the era of Free Trade. In payment by Telegraphic Transfer there are facilities and shortcomings, which deficiencies will be very bad both exporters and importers. There is another solution from the payment system other than Telegraphic Transfer, namely there is a Letter of Credit explained that the payment of this Letter of Credit equally guarantees its security to both parties, namely exporters and importers.